Possible mortality reduction by endoscopic sphincterotomy during endoscopic retrograde cholangiopancreatography: a population-based case–control study - Strömberg, Cecilia; Arnelo, Urban; Enochsson, Lars; Löhr, Matthias; Nilsson, Magnus (Surgical endoscopy, 2012)
Background Endoscopic retrograde cholangiopancreatography (ERCP) is widely used for young patients, but ERCP and endoscopic sphincterotomy in particular are reported to be associated with increased complication and mortality rates. This study aimed to calculate mortality and to identify risk factors for death within 90 days after ERCP for nonmalignant disease. Methods From the Swedish Hospital Discharge Registry, the authors identified all individuals in Stockholm County who had undergone in-patient ERCP during 1990–2003. Among these individuals, they excluded those recorded in the Swedish Cancer Registry as having a diagnosis of malignancy in the liver, pancreas, or bile ducts. Cases, defined as patients who had died within 90 days after the procedure, were identified by cross-linkage to the causes of death registry. Control subjects were randomly sampled from the same cohort. The medical records were studied to discern risk factors for death after ERCP. Results The mortality rate was 1.6%. Advanced age, severe comorbidity, high complexity of the procedure, and occurrence of a complication were associated with death within 90 days, whereas a previous cholecystectomy or the simultaneous performance of an endoscopic sphincterotomy reduced the risk. Conclusions Old age and comorbidity are the main risk factors for death after ERCP, but a complex procedure or the occurrence of a complication also seems to increase short-term mortality. The performance of a sphincterotomy may reduce the risk of death, possibly by facilitating adequate drainage. A previous cholecystectomy also may decrease the risk of death after ERCP.